Effect of different bedding material on redirected behaviour and vices of thoroughbred race horses housed in stalls (Indian Journal of Animal Production and Management, 2024)
Frustration arising from lack of social contact and inconsistent training method, insufficient roughages, erratic management practices and different bedding material leads to redirected behaviour and vices in stabled horses. Further there was a need to assess the relation between behaviour and vices related to prevalence of many stereotypes and redirected behaviour i.e., weaving, tongue rolling, resting in the stable corner, soil consuming, wood chewing and cribbing. The aim of current research work was to establish the importance of bedding on behaviour of horses. Fifteen each of privately owned, mares and stallions were selected for the study. They were kept in the boxes in which they were observed for a minimum of four weeks.  Recordings were made between 10:00 to 12 AM and 5:00 to 7:00 PM. There was an increase in the prevalence of abnormal behaviour (P
Keywords: Horses; Bedding material; Redirected behaviour; Vices